Improving hip fracture care: striving for excellence. Issue 3 (1st July 2013) - Nandi, N; Maddula, M; Sahota, O
Summary: Hip fracture is a common and potentially devastating injury that occurs mainly in older people. The incidence is predicted to rise by 30% in the next 10 years alone. Many of those who recover suffer a loss of mobility and independence. There is growing emphasis to improve the care of patients sustaining hip fracture, especially in those with concurrent cognitive impairment. This review focuses on current best practice as well as several key areas of management, including analgesia, anaemia and nutrition. In doing so, we hope to identify interventions that may form the basis of a future Enhanced Recovery Pathway dedicated to hip fracture care.